Informal Learning of Homeless Women: A Feminist Study of Surviving the Everyday - Carole E. Pearce (Adult Education Research Conference, 1999)
The purpose of this study was to examine how homeless women learned to survive in their daily lives. Their relationships contributed to many years of unsettling experiences and continuous transitional situations. Each woman followed a progression of sophisticated street smarts, but eventually faced a devastating decision which served as the impetus for a learning experience that resulted in an empowering change.